Customer perceptions of quality of service in public transport: Evidence for bus transit in Scotland. Issue 3 (September 2016) - Morton, Craig; Caulfield, Brian; Anable, Jillian
Highlights: Public transport users associate issues relating to convenience, cabin environment and ease of use to perceived quality of service. Perceptions of quality of service tend to vary across socio-economic cohorts. Perceptions of service convenience are central in evaluations of overall satisfaction with service. Abstract: This paper provides a detailed examination of a quality of service indicator utilised by the Scottish Government to assess the opinions of passengers towards bus transport. The quality of service indicator takes the form of an 11 item opinion scale which covers an array of service aspects. Factor analysis is employed to identify latent constructs which are present within this scale. Three latent constructs associated with attitudes towards perceived quality of bus service are identified, covering convenience, cabin environment and ease of use issues. These latent constructs are further explored through an appreciation of how attitudes towards perceived quality of bus service vary across socio-economic cohorts and the degree to which these attitudes can be of use in explaining variation in perceived satisfaction with the bus service. Results of the analysis suggest that attitudes regarding quality of bus service vary significantly across passenger groups, with females having a tendency to exhibit relatively negative opinions regarding the quality of the cabin environment with a similar finding observed in the case of passengers who are looking after the home and family. In addition, perceived convenience of the bus service appears to have a significant positive explanatory power over perceived satisfaction with the bus service, suggesting that improvements to service frequency, availability, reliability and stability will likely increase perceived satisfaction amongst existing passengers. At a more general level, this paper demonstrates the level of additional knowledge which can be attained through a more detailed analysis of existing transport policy data.